THE INFLUENCE OF TASK-BASED LANGUAGE TEACHING AND AUDIO-LINGUAL TEACHING APPROACH ON MANDARIN LANGUAGE LEARNING OUTCOMES - Wen, Chua Hui; Ying, Lin Chia; Azlan, Mohammad Affiq Kamarul (PEOPLE: International Journal of Social Sciences, 2018)
The aim of this study is to look into the influence of Task-based Language Teaching (TBLT) and audio-lingual teaching approaches on Malaysia tertiary level non-native Mandarin learners’ learning outcomes in the teaching of Mandarin as a global language. A quasi-experimental study was carried out on 43 Universiti Malaysia Kelantan students, where they were divided into two groups. Group A contained 21 students, while Group B had 22 students. The two groups were studied to compare the influence of the two different teaching approaches: TBLT (Group A) and audio-lingual teaching approach (Group B). Willis’ (2006) Task-based Learning Framework was applied as the teaching framework in Group A (TBLT), while dialogue memorisation was applied in Group B (audio-lingual teaching approach). The results of the teaching approaches were analysed using simulated oral test, where language fluency, language accuracy and language pronunciation were the elements the researcher looked into. The results of the findings showed that Group A indicated a drop in the learning outcomes’ mean score in the first cycle of the post-treatment test, but the condition changed in the second cycle post-treatment test and delayed post-treatment test, where the learning outcomes of Group A (TBLT) outperformed the control group’s (audio-lingual teaching approach). The finding of the research provides suggestions towards teachers to apply communicative task between non-native learners and native speakers to improve learners’ learning outcomes. It also advises teachers to apply TBLT in a longer term rather than in a short term.